Age Structure and Carbon Emission with Climate-Extended STIRPAT Model-A Cross-Country Analysis - Liu, Wan; Luo, Zhechong; Xiao, De (Frontiers in Environmental Science, 2022)
The driving role of population on GHG emissions has been an important research topic in academia, with the expiration of the second agreement period of the Kyoto Protocol in 2020 and the UNFCCC's continued requirement for parties to the Paris Agreement to submit new national autonomous contribution emission reduction targets thus makes it more important to better understand the factors influencing carbon emissions. However, most of the existing studies based on the IPAT framework, only addressed the impact of population size rather than its structure, which are not deep and specific enough. Based on the environmental EKU theory, we argue that age groups differs between income and consumption habits, and thus the emissions from their economic activities differs. To examine whether a heterogeneous effect of demographic structure on carbon emissions exists, this study set up the climate extended STIRPAT model, represents demographic structure by ratio of four main groups according to WPP, then uses relevant data from 182 countries worldwide during 1970-2018 for estimation. To aggregate climate indicators across a country, NASA nighttime lights data is used to weight the climate data from more than 30,000 weather stations. Panel Seemingly Unrelated Regression method were used to solve the problems of cross-sectional correlation, non-stationarity and endogeneity for that countries are closely linked in the global meteorological system. The empirical results show that the age structure had a significant impact on carbon emissions, the population aged 20-34 has the largest impact, the population aged 35-49 has the second largest impact, the impact of the population aged 50-65 is not significant but with negative impact on transportation carbon emissions, and a positive effect on electricity & heat carbon emissions. The threshold effect of per capita income on carbon emissions is confirmed to exist. The increase in population aging may lead to a significant decrease in total carbon emissions, even after taking into account the increase in electricity emissions due to cooling and heating demand.